The current state, problems and prospects for the development of organic agriculture in Ukraine - Pohrebskyi, Taras H.; Golub, Gennadii S.; Golub, Sergiy M.; Potapova, Alla H. (Wydział Nauk Przyrodniczych Uniwersytet Śląski Sosnowie, 2024)
The article is devoted to the development of organic agriculture in Ukraine. The authors describe the factors of development of organic agriculture. The study also considered the peculiarities of the current state of organic agriculture in Ukraine. Spatial differences in the development of organic agriculture in Ukraine have been clarified. Problems in organic agriculture are identified and divided into groups. External and internal factors of organic agriculture in Ukraine in the context of balanced development of rural areas were studied on the basis of the SWOT analysis. Prerequisites and prospects for the development of organic agriculture in Ukraine are determined.
Keywords: organic agriculture; development of rural areas; SWOT analysis; Ukraine